Optimization of Sharia Insurance Implementation and Supervision Based on Fatwas of the Indonesian Ulema Council - Jihan Husna Srifyan; Ishmah Afiyah (Demak Universal Journal of Islam and Sharia, 2024)
Implementation of sharia insurance for Hajj and Umrah travel by PT. Asuransi Syariah Mandiri Surabaya (ASMS) demonstrate success in integrating sharia principles in the travel insurance industry based on a review of Fatwa Majlis Ulama Indonesia (MUI). To find out the relevance of sharia insurance mashlahah for Hajj and Umrah travel PT. Asuransi Syariah Mandiri Surabaya (ASMS) with Fatwa Majlis Ulama Indonesia (MUI). Implementation of sharia insurance for Hajj and Umrah travel by PT. Asuransi Syariah Mandiri Surabaya (ASMS) covers several important points. First, the adoption of sharia principles in the preparation of Hajj and Umrah travel insurance products has provided a strong legal foundation for companies. PT. Asuransi Syariah Mandiri Surabaya (ASMS) carefully ensures that insurance products comply with Fatwa MUI's provisions, which allows insurance use by avoiding elements of riba and speculation. This demonstrates the company's commitment to sharia compliance and ensures that Hajj and Umrah pilgrims can avail protection without violating religious principles. Second, the implementation of sharia insurance for Hajj and Umrah travel by PT. Asuransi Syariah Mandiri Surabaya (ASMS) Positively meet the needs of pilgrims in the face of certain risks that may arise during the journey of worship. Overall, the implementation of sharia insurance for Hajj and Umrah travel by PT. Asuransi Syariah Mandiri Surabaya (ASMS) can be considered successful and relevant to the needs of the Muslim community. Taking into account aspects of sharia compliance and risk protection.